PERANAN LETTER OF CREDIT SEBAGAI ALAT MANAJEMEN RISIKO - Amelia Setiawan (Bina Ekonomi, 2007)
Organization manages risk in order to mitigate risk and uncertainty. They identify risks and minimize negative impact of those risks. Letter of Credit used to fund trading of goods and services between two parties who doesn't know each other. Letter of Credit often used in trading between countries. The reason why Letter of Credit can be classifying as an effective payment systems is because it is safe, for exporter or importer. Because of the safety of Letter of Credit, it is often used in international trading.